Recreational athletes during downhill-mountain biking (DMB) show high incidence of upper extremity fractures in combination with soft-tissue injuries - Franziska Lioba Breulmann; Claudia Krenn; Lukas Fraißler; Harald Kindermann; Michael Gattringer; Michael Stephan Gruber; Sebastian Siebenlist; Georg Philipp Mattiassich; Martin Bischofreiter (Scientific Reports, 2024)
Abstract Downhill-mountain biking (DMB) is a high-risk sport and often leads to several injuries, especially in non-professional athletes. We retrospectively analyzed the most common injuries and profiled the injury mechanism. Until now, there is no such analysis of injuries by non-professional mountain bike athletes. We collected patient data from patients who suffered from an injury during DMB. The inclusion criteria were (1) injury during the summer season of 2020 and 2021, (2) injury during off-road and downhill mountain bike sports activity, and (3) treatment at the Department of Traumatology of the Klinik Diakonissen Schladming. Patient data was analyzed regarding the type of injury, location of the injury, patient age and gender of the patients. Most patients with injury are at the age of 26–35. Second most are between 36 and 71 years old. The type of injury differs between age and gender. Mostly upper-extremity injuries occur with a high probability of shoulder injuries. In the elderly patients, we found additional injuries of the thorax and chest. To conclude, most common types of injuries are soft-tissue injuries, often in combination with fractures. The risk for injuries is higher for recreational athletes with different injury characteristics than professional athletes.